2020
DOI: 10.1177/0885328220963934
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antibacterial activity of a composite coating on titanium for dental implant application

Abstract: Dental implants are the most innovative and superior treatment modality for tooth replacement. However, titanium implants still suffer from insufficient antibacterial capability and peri-implant diseases remain one of the most common and intractable complications. To prevent peri-implant diseases, a composite coating containing a new antibacterial agent, (Z-)-4-bromo-5-(bromomethylene)-2(5H)-furanone (BBF) was fabricated on titanium. This study was designed to investigate the antibacterial activity of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Biomaterials have been remarkably developed over the last years, targeting improvements in tissue engineering, immunotherapy, and drug delivery sphere [ 43 , 44 , 45 , 46 ]. Biological response, especially to implanted materials, are major concern to successfully achieve regenerative purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterials have been remarkably developed over the last years, targeting improvements in tissue engineering, immunotherapy, and drug delivery sphere [ 43 , 44 , 45 , 46 ]. Biological response, especially to implanted materials, are major concern to successfully achieve regenerative purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some promising results using these coatings, newer implant methods are required due to the absence of long-lasting antibacterial effects and the emergence of drug-resistant microbes [37]. Previous studies have shown that TESPSA 27 , polydopamine, silver nanoparticles [28], BBF (a composite coating containing a new antibacterial agent (Z-)-4-bromo-5-(bromomethylene)-2(5H)-furanone) [38], as well as black phosphorus-zinc oxide nanohybrids [33], all have potential as antibacterial coatings for dental implant surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This feature of DAIs lays the basis for the development of antibacterial surfaces with long active durations. As shown by the representative reports on the development of “ long-term ” antibacterial surfaces ( Table 5 ) [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ], various ingredients such as commercial antibiotics (tigecycline, vancomycin, amoxicillin, etc.) [ 121 , 132 ], metals or metal ions (silver, copper, or zinc) [ 124 , 125 , 129 ], and other drugs [ 127 , 128 ] were taken to equip implantable biomaterials (titanium, silicone, ceramics, etc.)…”
Section: Innovative Designs To Mitigate Device-associated Infectionsmentioning
confidence: 99%